Novel mutations in the ABCD1 gene caused adrenomyeloneuropathy in the Chinese population - He, Raoli; Zhang, Jian; Huang, Tianwen; Cai, Guoen; Zou, Zhangyu; Ye, Qinyong (Frontiers in Neurology, 2023)
Background: As a rare genetic disease, adrenomyeloneuropathy (AMN) is the most common adult phenotype of X-linked adrenoleukodystrophy (X-ALD). Mutations in the ABCD1 gene have been identified to cause AMN. Methods: We applied the clinical evaluation, laboratory tests and neuroimaging on three patients with progressive spastic paraparesis. In genetic analysis, we investigated ABCD1 gene mutations by whole exome sequencing and Sanger sequencing. Bioinformatics tools were used to predict the effects of identified ABCD1 mutations on the protein. Results: All three patients were males with adult-onset disease, mainly characterized by progressive spastic paraparesis. Two patients had peripheral neuropathy. One patient had signs of adrenal insufficiency. All three patients showed cerebral involvement on brain MRI, while two patients were found with diffuse cord atrophy on spinal MRI. High VLCFA levels in plasma, as well as C24:0/C22:0 and C26:0/C22:0 ratios were found in all three patients. In addition, three different ABCD1 mutations were identified in three unrelated Chinese families, including one known mutation (c.1415_1416delAG) and two novel mutations (c.217C>T, c.160_170delACGCAGGAGGC). Based on the clinical assessment, radiographic, biochemical and genetic testing, the final diagnosis was AMN in these patients with spastic paraparesis. Conclusion: This study reported three AMN patients and identified two novel mutations in the ABCD1 in the Chinese population. Our finding emphasized that X-ALD is an important cause of adult-onset spastic paraplegia. Thus, neuroimaging, VLCFA testing, and especially the detection of ABCD1 gene have important implications for the etiological diagnosis of adult patients with spastic paraplegia.